The Public e-Procurement in Malaysia. - Othman, Rohana; Jusoff, Kamaruzaman; Zakaria, Husein; Nordin, Norlaili; Shahidan, Zamzam (Institute of Interdisciplinary Business Research, 2009)
Public procurement in Malaysia in echoing a global phenomenon has become increasingly afflicted with corruption. If allowed to go unchecked, corruption will threaten the national foundation with a multitude of negative impact like underperformance, over-billing, elimination of fair competition, decreased efficiency and the ensuing dilapidated cost-effectiveness, amongst a plethora of other undesirables. The proliferation of the internet and the World Wide Web technology has enabled the migration of traditional manual paper-based public procurement procedures to electronically-based systems. This paper lauds the affirmative action approach adopted by the Government of Malaysia to address the spectre of corruption via e-procurement. The e-procurement, now referred to as e-perolehan, was a flagship project launched in the Multimedia Super Corridor (MSC) in 1996. The arguments tabled in this paper expound the benefits to be garnered through the implementation of e-procurement. However, as the case normally is when matters involve national interests, things are never open and shut. Thus, in looking at both sides of the argument, this paper also outlined several cautionary arguments on the implementation of e-procurement. This paper supported the Malaysian government's decision to endorse e-procurement as a concerted effort to advocate transparency, accountability, integrity, curtailment of fraud and all that are key components to the principles of good governance.